203 Seven-Year Update of Multicenter Prospective Study of Large Vestibular Schwannomas: Acoustic Neuroma Subtotal Resection Study. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Monfared, Ashkan; Corrales, Eduardo; Theodosopoulos, Philip V.; Blevins, Nikolas; Oghali, John Steven; Selesnick, Samuel H.; Lee, Howard; Gurgel, Richard; Hansen, Marlan; Nelson, Rick F.; Gantz, Bruce; Kutz, Walter; et al.
Abstract: INTRODUCTION: Patients with large acoustic neuromas are at high risk of poor facial nerve (CNVII) function following surgery. Subtotal resection has the potential for better facial nerve outcome but higher tumor recurrence. METHODS: Patients with acoustic neuromas = 2.5 cm underwent gross total (GTR), near total (NTR) with remnant tumor no larger than 0.5 cm 3 on postoperative magnetic resonance imaging (MRI) or 2 × 2 × 5 mm residual in surgery, or subtotal (STR) resection defined as any larger remnant. Patients received stereotactic radiation if tumor remnant grew. RESULTS: Of 132 enrolled patients, 73 had at least 1-year follow-up (mean 38 months). Average age was 48.7 years, mean tumor diameter was 3.33 cm, and 34% were cystic. As defined by postoperative MRI, 12 had GTR, 22 NTR, and 39 STR. There were 14 (21%) recurrences, 1 (8%) in GTR, 2 (9%) in NTR, and 11 (28%) in STR groups with average of 35 months to recurrence (4-74 months). The recurrences were treated with SRT in 11 cases, intensity-modulated radiation therapy in 1 case, and surgery in 2 cases due to size and cystic nature of recurrence. Four post-radiation remnants (33%) continued to grow and required surgical salvage. Tumor recurrence was related to longer follow-up, non-cystic tumor, larger residual tumor, and STR resection. Good facial nerve function (House-Brackmann I and II) was achieved in 67% immediately and 81% at 1-year from surgery. Better immediate but not late nerve function was associated with smaller preoperative tumor size and residual tumor left behind. CONCLUSION: Less-than-total resection of large acoustic neuromas allows for excellent facial nerve outcomes; however, the rate of persistent growth is inversely proportional to the size of residual tumor. Growing tumor remnants may be treated effectively with stereotactic radiation, though about 1/3 of tumors may still require surgical salvage. The NTR group had slightly better CNVII outcome compared to GTR without increased risk of recurrence.